Monetary policies, banking systems, regulatory convergence, efficiency and growth in the Mediterranean - Ayadi, Rym; Mouley, Sami.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Monetary Policy, central banking, and international norms and regulations; a discussion far from new, nor applying exclusively to the world's most advanced economies. A sound monetary policy and a well-enforced regulatory regime is provided, in explanation of developing nations to channel financial resources more efficiently into investments.
Keywords: Banking law -- Mediterranean Region; Banks and banking; Economic development -- Mediterranean Region